A computational study of mucociliary transport in healthy and diseased environments. Issue 1 (4th March 2017) - Guo, Hanliang; Kanso, Eva
Abstract: Mucociliary clearance is the primary defense mechanism that protects the airways from inhaled toxicants and infectious agents. The fluid medium is spatially non-homogenous, consisting of a viscoelastic mucus layer on top of a nearly-viscous periciliary layer surrounding the motile cilia. In healthy environments, the thickness of the periciliary layer is comparable to the cilia length. Perturbations to this system are directly linked to infection and disease. Clinical evidence links the periciliary layer depletion to reduced rates of mucus clearance. Here, we develop a computational model to systematically study the effects of the viscoelastic properties and thickness of the mucus layer on the system's performance. We find that, compared to a control case with no mucus, a healthy mucus layer enhances the cilia performance: it improves flow transport at an energetic advantage to the cilia. In contrast, when the periciliary layer is depleted, mucus hinders transport and stiffer mucus leads to a substantial decrease in transport efficiency. This decrease in transport is accompanied by an increase in the cilia internal forces and power needed to complete the cilia beating cycle. We conclude by commenting on the relevance of these findings to understanding mucociliary transport in healthy and diseased environments.